Frontal fibrosing alopecia and genital Lichen sclerosus: Single‐center experience. (9th August 2020) - Grassi, Sara; Tadiotto Cicogna, Giulia; Magri, Francesca; Caterina Fortuna, Maria; Caro, Gemma; Pernazza, Angelina; Soda, Giuseppe; Miraglia, Emanuele; Giustini, Sandra; Carlesimo, Marta; Rossi, Alfredo
Abstract: Background: Despite the incidence of Frontal fibrosing alopecia (FFA) has been increasing in last two decades, the pathophysiology and trigger factors of FFA have not been yet fully understood. Aims: The aim of this study was to describe epidemiology, clinical and trichoscopic features and comorbidities of FFA patients, in order to improve the understanding of this disease. Patients/Methods: A retrospective, observational monocentric study was conducted from 2003 to 2019. Data concerning epidemiology (age, gender, age of menopause, and age of FFA onset), comorbidities, current therapies, localization of FFA (such as frontotemporal hairline, occipital, eyebrow, eyelash, beard, sideburns, and body hair), presence of papules and sign of Lichen planus (LP) at skin, mucosae and/or nail were collected for each patient included. Results: A total of 119 Caucasian, adult patients (8 men and 111 female) with FFA were enrolled in the study. Cutaneous, mucosal, or nail localization of LP were found in 16% of our subjects. Interestingly, 15 out of 119 subjects (10.61%) were affected by concomitant genital Lichen sclerosus (LS) and 5 out of these 15 patients (4.38%) presented both LS and LP in association with FFA. Conclusion: Considering the high prevalence of LS in FFA patients in our case series, and the frequency of autoimmune comorbidities in both LS and FFA, it is possible to hypothesize an autoimmune process in both conditions. Further studies are needed for a better understanding of the nature of the association between LS and FFA.